Protective Effect of Fish Oil Supplementation on DNA Damage Induced by Cigarette Smoking (Journal of Health, Population and Nutrition, 2013)
The study examined the influence of fish oil (FO) supplementation on serum 8-hydroxy-2-deoxyguanosine (8-OHdG) levels as indicated by DNA damage markers and total antioxidant capacity (TAC) among male cigarette smokers. This double-blind, placebo-controlled randomized study was conducted among healthy cigarette smokers (n=40) who were part of a larger prospective cohort study. Twenty smokers were randomly selected to receive FO for 3 months (1 g/day), and another 20 smokers received a placebo for 3 months; 8-OHdG and TAC levels were measured in blood samples before and after the intervention. Serum 8-OHdG significantly decreased (p=0.001) and TAC increased (p